Judges - Spronk, Klaas (Historical commentary on the Old Testament, 2019)
This commentary presents a new approach to the old problems of the dating of the book of Judges and the reconstruction of the way different sources were used. It wants to show that the book of Judges can be read as the work of one literary talented author living in the early Hellenistic period. With materials from different sources he wrote his book as introduction to the history of the kings of Israel as can be found in the books of Samuel and Kings with a clear view on leadership and on the relation between the leader and YHWH. Next to the reconstruction of the historical background of the book and its author, much attention is paid to the history of interpretation, from the earliest retellings to the newest interpretations